IDEOLOGIA E QUESTIONAMENTO EM MAFALDA AMAZ'ONA, DE MARGARIDA PATRIOTA (Polifonia, 1994)
ABSTRACT: The aim of this paper is to present one of the possible ways of reading/interpreting the childern's book "MAFALDA AMAZ'ONA", written by Margarida Patriota. It focuses mainly on the scope of ideology.